Water-Soluble Total Flavonoids Isolated from Isodon lophanthoides var. gerardianus (Benth.) H. Hara Promote Hepatocellular Carcinoma Sensitivity to 5-Fluorouracil. (19th July 2021) - Feng, Chuan-Ping; Ding, Hai-Xia; Liu, Ying-Xin; Di, Qing-Feng; Liu, Yan; Liang, Jian; Liu, Guang-Xi
Abstract : Isodon lophanthoides var . gerardianus (Benth.) H. Hara, a native medicinal plant produced chiefly across Southern China, is one of the mainstream varieties of Xihuangcao, which has long been applied in preventing and treating some common liver or gall diseases. Water-soluble total flavonoids (WSTF) extracted from folk herbal medicine have many pharmacological effects. The objective of the paper is to investigate the synergy of WSTF with 5-ﬂuorouracil (5-FU) on HCC and the related mechanisms. Cells were exposed to WSTF alone or combination treatment with 5-FU. Then, in this study, we conducted cell viability test, cell cycle and clone forming test, apoptosis assay, reactive oxygen species (ROS), Western blotting, immunohistochemistry, and a xenograft tumor growth model for investigating the role of WSTF in HCC in vivo and in vitro . It was discovered that WSTF caused cell cycle arrest at the G 0/ G 1 phase while increasing the ROS contents. The generation of ROS levels could cause cell apoptosis and inhibit colony formation. WSTF decreased the Bcl-2 level but promoted the Bax level. These showed the mitochondrial dependence of WSTF-mediated apoptosis. WSTF combined with 5-FU have a synergistic effect to significantly inhibit carcinogenicity in vivo and in vitro . The reduced ROS changed the synergy of WSTF with 5-FU. At last, WSTF inhibit the growth of HCC and promote the HCC sensitivity to 5-FU through ROS accumulation. WSTF-increased ROS levels may partially or completely contribute to enhanced toxicity. WSTF combined with 5-FU in HCC can play a synergistic effect when applied in the clinical setting.